DIVERSIFICATION OF PINEAPPLE WASTE THROUGH ECO-ENZYME DOING TRAINING AT THE “QUEEN” PINEAPPLE FARMER GROUP KEDIRI - Tri Ana Mulyati; Fery Eko Pujiono; Umul Farida (Yayasan Education and Social Center, 2023)
Kediri is the largest honey pineapple-producing area in East Java, so it has pineapple farmer groups. The honey pineapple farmer group called